How America Got it Right : The U.S. March to Military and Political Supremacy - Alexander, Bevin (New York Crown Forum, 2005)
Left-wing critics - both at home and abroad - relish blasting our country for being the world's sole superpower, or even an "imperialist" power. But as acclaimed military historian Bevin Alexander shows in this book, these criticisms are completely off the mark. Alexander reveals how the United States has done and continues to do exactly the right thing in military and foreign affairs. As the world's dominant political force and military power, he says, we are the only nation that will actually go into the world and strike down evil. And we must not shirk that responsibility - especially because we cannot rely on our so-called allies to defend our freedoms. Alexander tells the dramatic and sometimes surprising story of how, from the American Revolution to the War on Terror, America's core principles and ideals have shaped our march to economic, military, and political supremacy
Include Notes and Index
Keywords: Military policy -- National characteristics, American